Military High Explosives - Jörg Mathieu; Hans Stucki (CHIMIA, 2004)
Military high explosives are safe to handle, have a long shelf life, their energy density is high and the propagation of the explosion (detonation reaction) is very fast. The energetic compounds are combined with polymers and other substances to match the properties as required. To initiate a detonation, a shock wave is needed. This is accomplished with a small quantity of a primary explosive. Modern, extremely insensitive formulations have been developed in most countries to eliminate accidents with ammunition. Apart from insensitive energetic compounds, new inert or energetic binder systems will be introduced to improve the vulnerability. The search for new energetic materials with highest performance characteristics is a never-ending task.